Constraints on Dark Matter with Gamma-Ray Experiments and Future Observational Strategies - Morselli, Aldo (Frontiers in Physics, 2017)
Indirect dark matter (DM) searches rely on detection of stable by-products of DM interactions to search for a signal of this elusive component of the Universe. Among these final products, gamma rays have recently played a major role in understanding the nature of the DM particle. We review the current status of indirect DM searches with gamma-ray observations and prospects with future instruments.